Effect of mulching on cabbage grown in the Mexicali Valley - Escobosa-García, Isabel; Vázquez-Medina, María Magdalena; Samaniego-Gámez, Blancka Yesenia; Valle-Gough, Raúl Enrique; Vázquez-Angulo, Juan Carlos; Núñez-Ramírez, Fidel (Revista Mexicana de Ciencias Agrícolas, 2022)
The use of mulch in soil to produce vegetables increases the yield and quality of harvested products; however, these increases are conditioned by the type of mulch, whether plastic or organic. An experiment was performed in cabbage (Brassica oleracea L. var Capitata) culture during the 2021-2022 season, with the aim of evaluating its response on water use efficiency, mineral nutrition and yield to four types of mulches in the soil. Four treatments were evaluated (soil with black plastic mulch, white plastic mulch, mulch with wheat straw and a control without mulching), distributed under a randomized block design with four repetitions. The results showed that white plastic mulch increased the total biomass, cabbage weight and leaf weight, compared to the rest of the treatments. The use of both plastic mulches (black and white) increased the concentration of nitrates in the cell extract of the midrib. The leaf temperature increased only due to the use of black plastic mulch. Finally, the efficiency in the use of water was higher in the treatments with plastic mulch and lower in the soil without mulching. Considering the greater efficiency in the use of water, yield and mineral nutrition, it was concluded that the soil with plastic mulch is the most recommended to produce cabbage in the Mexicali Valley, Mexico.
Keywords: Brassica oleracea L; irrigation water; mineral nutrition; plasticulture